Removal of Pb(II), Cu(II), Cd(II), Cr(VI), methylene blue dye (MB) and inhibition of bacteria growth using modified fennel seeds from aqueous solutions - Mabungela, Ntandokazi (Vaal University of Technology, 2022)
Water contamination with pollutants like toxic heavy metals, dyes and pathogens is currently a global problem. Toxic heavy metals and dyes are not degradable and persist in environment, while pathogens are responsible for waterborne disease problem. Therefore, it is crucial to remove these pollutants from wastewater. Hence, this work reports mono, binary and ternary adsorption of copper-Cu(II), cadmium-Cd(II), lead-Pb(II), chromium-Cr(VI), methylene blue dye-MB and antimicrobial studies against Escherichia coli (E. Coli) and Staphylococcus aureus (S. aureus) and the resultant activated carbon (AC) was treated with potassium permanganate (KMNO4) from aqueous solution by pristine and modified fennel seeds. Pristine fennel seeds (PFS) were modified with acidic solution of hydrochloric acid (HCl), nitric acid (HNO3), sulphuric acid (H2SO4), phosphoric acid (H3PO4) and alkaline solutions of sodium hydroxide (NaOH) and calcium hydroxide (Ca(OH)2). PFS were also carbonized at different temperature of 500, 600 and 700 ℃ and treated AC obtained with potassium permanganate (KMNO4). Lastly, fennel seeds were incorporated with iron(III) oxide nanoparticles (Fe2O3 NP), iron(III)-1,2,3,4-tetracarboxylic acid (Fe-TCA) and binary nanoparticles of CuO-ZnO in a ratio of 1:2 & 2:1. Fennel based adsorbents were characterized using Scanning Electron Microscope with Energy Dispersive Spectroscopy- (SEM-EDS), Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), Ultraviolet-Visible Spectroscopy (UV-Vis), Transmission Electron Microscope (TEM), Thermogravimetric Analyser (TGA) and Brunauer-Emmett-Teller (BET). The SEM results showed that the surface morphology of the fennel based adsorbents became more porous with cavities compared to PFS. The FTIR results revealed that the adsorbents surface had hydroxide (-OH), carbonyl (-C=O) and carboxyl (-COOH) functional groups. XRD results showed a diffraction peaks around 19 ⁰ and 23 ° which are attributed to the presence of cellulose. TEM images of the composites indicated deposits of nanoparticles on the surface of fennel seeds. TGA results showed a weight loss around 205-556 ℃ for PFS and 205-507 ℃ for composites and that was due to breakdown of lignocellulosic material in fennel seeds. The physicochemical characteristics such as cation exchange capacity (CEC) and Brunauer, Emmett and Teller (BET) surface area were enhanced after impregnation when compared with PFS. The adsorption of Cr(VI) and growth inhibition of Escherichia coli and Staphylococcus aureus on binary nanoparticles of CuO-ZnO were investigated. The binary CuO-ZnO nanoparticles were prepared through co-precipitation method. The highest adsorption capacity recorded at pH 2 and 308 K were 75.96 and 84.77 mg/g for FS/CuO-ZnO[1:2] and FS/CuO-ZnO[2:1], respectively. The antibacterial assays indicated that the materials are effective in preventing the growth of microbial growth. Removal and photo-degradation of methylene blue dye from aqueous solution using FS-NP and FS-TCA composites were examined. The maximum adsorption capacity recorded for PFS was 13.21 mg/g while for FS-NP and FS-TCA was 32.84 and 42.89 mg/g, respectively. PFS showed no activity for photocatalytic degradation properties while PF-NP and PF-TCA recorded 58.97 and 48.62 % efficiencies, respectively. The ternary removal of metal ions of copper Cu(II), lead Pb(II), and methylene blue (MB) dye on pure and acid treated fennel seeds biomaterials from aqueous solution by batch adsorption was investigated. Pure fennel seeds were labelled (PFS), nitric and sulphuric treated seeds were labelled (NAFS) and (SAFS) respectively. Adsorption data showed that all biomaterials had a higher affinity for MB dye more than Pb(II) and Cu(II) metal ions. The maximum adsorption capacities onto PFS were 6.834, 4.179 and 2.902 mg/g; NAFS 15.28, 14.44 and 4.475 mg/g; while for SAFS 19.81, 18.79 and 6.707 mg/g respective for MB dye, Pb(II) and Cu(II) ions. Binary adsorption of Copper (Cu(II)) and Chromium (Cr(VI)) from aqueous solution using activated carbon-AC and AC functionalized with KMnO4 derived from fennel seeds was examined. Activated carbon-AC from fennel seeds was obtained at different temperatures of 500, 600 and 700 °C and the results were named FS-500, FS-600 and FS-700. Thereafter, each sample was chemically treated with KMnO4 solution to obtain KMFS-500, KMFS-600 and KMFS-700. The results showed that the KMFS-700 and FS-700 adsorbed more than KMFS- 600, KMFS-500, FS-600 and FS-500 for both Cu(II) and Cr(VI) metals. The maximum adsorption capacity on FS-700 was 19.886 mg/g and 8.510 mg/g for Cu(II) and Cr(VI) whilst on FS-600 were 15, 423mg/g and 1.202 mg/g and on FS-500 were 16. 921mg/g and 1.722mg/g, respectively. The maximum adsorption capacity on KMFS-700 was 19.786 mg/g and 10.572 mg/g for Cu(II) and Cr(VI) whereas on KMFS-600 were 15, 735mg/g and 8.109 mg/g and on KMFS-500 were 17. 648 mg/g and 3.479mg/g, respectively. Binary adsorption of toxic metal ions of Cu(II) and Pb(II) from aqueous solution by pristine and modified fennel seeds was studied. Pristine fennel seeds (PFS) were chemically treated with acidic and alkaline solutions to develop modified adsorbents designated ATFS and BTFS respectively. The maximum uptake of Cu(II) and Pb(II) on PFS was 3.345 and 11.524 mg/g. While for ATFS 3.78 and 13.07 mg/g, and BTFS 8.143 and 14.85 mg/g, respectively Simultaneous removal of copper Cu(II), cadmium Cd(II), and methylene blue dye (MB) from an aqueous solution using PFS and modified fennel seeds was investigated. The pristine fennel seeds (PFS) were chemically treated with phosphoric acid (H3PO4) and calcium hydroxide (Ca(OH)2) solutions to produce H3FS and CaFS, respectively. The maximum adsorption capacity for Cu(II) by PFS, H3FS and CaFS was 7.208, 5.504, and 5.791 mg/g, respectively. For Cd (II) by PFS, H3FS and CaFS, it was 2.274, 5.021 and 12.3 mg/g, respectively. The maximum adsorption capacity of MB by PFS, H3FS and CaFS was 11.114, 4.071 and 18.468 mg/g. This thesis is written in an artile format.
Ph. D. (Department of Biotechnology and Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Water contamination; Pollutants; Toxic heavy metals, dyes and pathogens; Bacterial growth; Adsorption; Inorganic and organic contaminants; Water pollution; Removal of wastewater pollutants; Dissertations, Academic -- South Africa.; Water -- Purification -- Biological treatment.; Adsorption.